Internet of Things (IoT) based Electrical Power Monitoring System for Solar Power Plants using the Telegram Application - Rezi Delfianti; Venny Aminda Tazayul; Bima Mustaqim; Fauzan Nusyura; Catur Harsito (Universitas Negeri Surabaya or The State University of Surabaya, 2025)
Indonesia, with its tropical climate, possesses substantial solar energy potential. However, traditional monitoring of solar power systems in Indonesia still relies on manual observation, making the process inefficient, time-consuming, and prone to error. To address these limitations, this study proposes the design and implementation of a real-time Internet of Things (IoT)-based monitoring system for solar power plants using the Telegram application as the user interface. The system integrates the ESP32 microcontroller and the Pzem-004 T sensor to measure AC electrical parameters, including voltage, current, power, energy, frequency, and powerfactor. Unlike previous studies that used platforms such as Blynk or ThingSpeak, this research introduces Telegram as an innovative messagingbased monitoring platform, offering greater accessibility, simplicity, and user familiarity. The monitoring system was tested on a single-phase off-grid solar power setup, utilizing five types of household electrical loads, to validate its accuracy and reliability. The ESP32 communicates with the Telegram bot through Wi-Fi, and users can retrieve real-time data via predefined commands. Experimental results demonstrate high measurement accuracy, with average errors of 0.07% for voltage, 0.1% for current, and 0.08% for power. These results confirm that the system provides reliable data transmission and sensor readings. This work contributes a low-cost, efficient, and user-friendly alternative to conventional monitoring systems, particularly for decentralized renewable energy systems in remote or off-grid areas. The integration of Telegram as a communication medium for energy monitoring adds a novel dimension to IoT-based power system applications.